Regional differences, distribution dynamics and convergence of multi-dimensional grain security level in major grain producing areas in China - Jing Cheng; Jiaqi Guo (PLoS ONE, 2026)
Based on panel data from China’s 13 major grain – producing provinces between 2014 and 2023, this study constructs a multidimensional grain security evaluation index system, incorporating the dimensions of quantity, quality, ecology, and capacity. Using the entropy method, kernel density estimation, Dagum Gini coefficient, and convergence model, we analyze the regional differences, dynamic evolution, and spatial convergence of grain security levels. The results show that: (1) grain security level is generally increasing; there are obvious spatial differences in grain security level among; (2) There are obvious spatial differences in grain security levels among regions, showing the trend of “Northeast> central> eastern> western”; (3) α Convergence analysis shows that the central region converges, while the northeast, east and west regions diverge; both absolute β convergence and conditional β convergence exist in the whole region and each region. Compared with previous studies, this paper provides new insights into the dynamic evolution, spatial distribution and regional convergence of multidimensional grain security in China’s major grain producing areas by integrating a multi-dimensional framework including quantity, quality, ecology and capacity. The research has enriched the evaluation system of grain security and laid a solid foundation for policy optimization.